An Electricity Price Modeling Framework for Renewable-Dominant Markets - Martin Hain; Hans Schermeyer; Marliese Uhrig-Homburg; Wolf Fichtner (Karlsruhe Institute of Technology (KIT), Institute for Industrial Production (IIP), 2017)
Renewables introduce new weather-induced patterns and risks for market participants active in the energy commodity sector. We present a flexible framework for power spot prices that is capable of incorporating a weather model for the joint distribution of local weather conditions. This not only allows us to make use of a long history of local weather data in the calibration procedure but also makes it possible to assess how changes in the renewable generation portfolio impact the characteristics of future wholesale spot prices. Empirical tests demonstrate the model's capability to reproduce salient features of market variables. We furthermore show why our model offers unique benefits for market players compared to existing approaches.
urn:nbn:de:swb:90-712356; More recent version: http://hdl.handle.net/10419/267803
Keywords: 330